Pemanfaatan Maggot (Hermetia illucens) Sebagai Pakan Alternatif Dengan Kombinasi Pakan Pelet Terhadap Pertumbuhan Dan Sintasan Ikan Gabus (Channa striata) - Fitriani Fitriani; Helmi Haris; Rih Laksmi Utpalasari (Universitas PGRI Palembang, 2023)
One alternative to reduce the use ofÂ Cork fish (Channa striata) feed can be given an alternative feed, namely magot (Hermetia illucens) which is expected to accelerate fish growth and reduce production costs. The purpose of this study was to determine the effect and best treatment of the combination of feeding maggot and pellet feed with different proportions on growth, survival and efficiency of Cork fish (Channa striata) feed. This research was conducted for 60 days from November to December 2019 at SMK Unggul Negeri 2 Banyuasin III Sekojo Ujung Ring Road, Kedondong Raye Village, Banyuasin III District, Banyuasin Regency. This study used a completely randomized design (CRD) with 4 (four) levels of treatment, each treatment was carried out 3 (three) times, namely P1 (100% pelletized feed), P2 (75% pelleted feed and 25% maggot. ), P3 (Feeding pellets of 50% and 50% of maggot), P4 (Giving pellets of 25% and 75% of maggot). The container used in this study is a tarp pool. The results showed that the best growth in weight, length and survival rate for snakehead fish was found in treatment P4 with a weight of 3.78 grams, a length of 3.06 cm and a survival rate of 83.33%.